Englist - Rusdi, Muhammad; Daulay , Nurussakinah; Mahariah, Mahariah (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Character education has become one of the main focuses in the national education system and Islamic education in Indonesia because the increasingly complex challenges of the times demand the emergence of a generation that is not only intellectually intelligent but also strong in moral, spiritual, and social aspects. This study aims to analyze the forms of integration of Islamic educational values applied in the character building of students. The Islamic educational values integrated into the educational process in the character building of students at vocational schools in Medan City. The research methodology used is descriptive qualitative with a multi-site approach at vocational schools in Medan City, namely SMK Asga Mandiri and SMK Al-Razi. Data was collected through in-depth interviews, observations, and document studies, analyzed thematically through reduction, categorization, and interpretation, with triangulation validation. The results of the study show that the integration of Islamic educational values in vocational schools in Medan, particularly at SMK Asga Mandiri and SMK Al-Razi, is carried out through three main pillars: learning, habituation, and school culture. Spiritual, moral, social, and professional values are internalized in all educational activities. Teachers play a central role as role models and spiritual guides in instilling Islamic values in a contextual manner. Despite facing obstacles such as environmental influences and limited resources, this integration has a significant impact on improving students' religiosity, discipline, honesty, and responsibility, as well as shaping their character to be noble, ethical, and have Islamic integrity. The integration of Islam through learning, habituation, and school culture is effective in shaping students' character to be moral, disciplined, and have Islamic integrity